Comparison of laparoscopic versus open radical antegrade modular pancreatosplenectomy for pancreatic cancer: A systematic review and meta-analysis. (July 2022) - Tang, Wei; Zhang, Yu-Fei; Zhao, Yu-Fei; Wei, Xu-Fu; Xiao, Heng; Wu, Qiao; Du, Cheng-You; Qiu, Jian-Guo
Abstract: Background: Laparoscopic radical antegrade modular pancreatosplenectomy (l-RAMPS) provides a new surgical approach for patients with pancreatic cancers of the body and tail. However, whether it can achieve comparable outcomes to the open RAMPS (o-RAMPS) remains an issue. Methods: To evaluate the safety and effectiveness of l-RAMPS, the studies in the databases of Medline, Embase, and the Cochrane Library published before September 13, 2021 were searched and a meta-analysis was performed using the 2020 Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guideline. The perioperative and oncological outcomes were analyzed. Results: Five retrospective cohorts involving 189 patients were included for final pooled analysis. There were no significant differences in the patients' operation time, intra-abdominal bleeding rate, intra-abdominal infection rate, mild morbidity (Clavien-Dindo classification = 1), moderate to severe morbidity (Clavien-Dindo classification ≥2), overall morbidity, wound infection rate, pancreatic fistula rate, delayed gastric emptying rate, reoperation rate, length of hospital stay, postoperative mortality, R0 resection rate, and 2-year overall survival between the 2 approaches. Besides, l-RAMPS was associated with less blood loss (mean difference (MD) = −232.69, 95% confidence interval (CI) = −316.93 to −148.46, P < 0.00001) and shorter days until oral feeding (MD = −0.79, 95% CI = −1.35 to −0.22, P = 0.006). However, the pooled analysis also indicated a significantly fewer lymph nodes dissected (MD = −3.01, 95% CI = −5.59 to −0.43, P = 0.02) in l-RAMPS approach. Conclusions: Although l-RAMPS provides similar outcomes associated with benefits of minimal invasiveness compared to o-RAMPS, it harvested significantly fewer lymph nodes which might have potentially negative influence on the patients' long-term survival. L-RAMPS is still in the infancy stage and further investigation is needed to verify its feasibility. Highlights: First meta-analysis about laparoscopic radical antegrade modular pancreatosplenectomy (l-RAMPS) and open RAMPS (o-RAMPS). L-RAMPS was comparable with o-RAMPS associated with advantages of minimal invasiveness. L-RAMPS harvested significantly fewer lymph nodes which might have potentially negative influence on patients' survival.